Lanthanide complexes of macrocyclic derivatives useful for medical applications - Delgado, R (2015)
The protonation constants of two series of tetraazamacrocyclic ligands with acetate and methylphosphonate pendant arms, as well as their stability constants with Cu2+, La3+, Sm3+, and Ho3+, were determined. All the values were determined in aqueous solution at 298.0 K and 0.10 mol dm(-3) in N(CH3)(4)NO3. In the first series, the effect of both types of pendant arms was observed by appending them in the same macrocyclic backbone, a 14-membered tetraazamacrocycle containing pyridine (ac(3)py14, p(2)py14, and p(3)py14). In the second series, two effects were taken into account, the increase of the cavity size of the macrocycle, from 12- to 14-membered, and the appending of acetate (dota, trita, and teta) or methylphosphonate (dotp, tritp, and tetp) arms. The ligands containing methylphosphonate arms have higher thermodynamic stability compared to the corresponding ones with acetate arms. especially in the series of compounds containing pyridine, even upon correction of the different basicity values of the ligands. On the other hand, the ligands with smaller macrocyclic cavity size, namely, dota and dotp, exhibit the largest values of stability constants. In contrast, ac(3)py14 presents low stability constants with lanthanides. Ail interpretation of these features based on the known adopted arrangement of dota and teta when free or coordinated with lanthanides is evaluated.